Pitfalls in single stock futures - Varma, Jayanth (London : SAGE Publications Ltd, 2017)
The case describes two episodes where the basic valuation model (cost of carry model) for single stock futures appears to break down. The first involves market manipulation and the second involves an unexpected change in the record date for an already announced dividend. This breakdown leads to large losses for the participant in these futures markets. The case describes two episodes where the basic valuation model (cost of carry model) for single stock futures appears to break down. The first involves market manipulation and the second involves an unexpected change in the record date for an already announced dividend. This breakdown leads to large losses for the participant in these futures markets.
Originally published: Varma, J. (2013). Pitfalls in Single Stock Futures. F&A0508. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Single stock futures -- Case studies; Speculation -- Case studies; Futures market -- Case studies